Not So Funny Business: Sexual Harassment in Stand-Up Comedy - Hansen, Briana (Workandmoney, 2017)
Up-and-coming Los Angeles comedian reflects on her experience of assault among some of the funniest people on the planet
Keywords: Sophie-Anne

ReadTheCode.ca - Canadian Creative Industries (2017)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

"They're Only Laughing 'Cause You're Pretty": Women's Experiences at Comedy Clubs - Lopez, Victoria Angelina (2017)
Stand-up comedy, like many forms of public entertainment or workplace organizations, is a field dominated by men. The deeply embedded perception that women are not funny, or not as funny as their counterparts, allow men’s privileged position in pursuing their career in comedy without their humor being questions based on their gender. However, the women’s’ experiences were found to be challenging with women’s humor being questioned and overshadowed by a hostile environment of sexual harassment. This disparity in the number of women represented in comedy is even more prevalent when it comes to the number of women who participate in stand-up comedy at the amateur level of open mic nights. This thesis examines gender disparity among comedians, the prejudices and discrimination women comedians face at the level of amateur comedian, and how they navigate through those barriers in comedy. Based on the findings from 14 in depth-interviews with 7 men and 7 women comedians, as well as observations of open-mic nights, this study investigates their experiences and perceptions of gender politics in comedy.
ISBN: 9780355540321
Keywords: Comedy clubs; Communication and the arts; Social sciences; Sophie-Anne